A CROSS-SECTIONAL STUDY ON THE SOCIO-DEMOGRAPHIC AND CLINICAL CHARACTERISTICS OF THALASSEMIA PATIENT’S IN QUETTA, BALOCHISTAN - Shafi Muhammad Khosa; Syed Muhammad Ishaque; Ziauddin; Muhammad Afzal Khan; Abdullah Jan Panezai; Zahid Mustafa; Ikram Din Ujjan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: To find out the socio-demographic and clinical profile of individuals with Thalassemia in Quetta, Balochistan. Thalassemia is a genetic blood disorder, characterized by improper synthesis of alpha and beta globin proteins of hemoglobin.Methods: A cross-sectional study was conducted from January 2019 to December 2021 at Thalassemia Centers of Bolan Medical Complex and Provincial Sandeman Civil Hospitals, Quetta. A questionnaire was used to collect the data from 306 (N) β-Thalassemia patient’s aged